The utilization of digital diplomacy in post-pandemic Korean tourism recovery efforts - Rostineu, Rostineu; Puri, Sinta Sari Sekar (Journal of Korean Applied Linguistics, 2024)
Tourism is one of the country's revenues sectors that was most affected after the outbreak of the COVID-19. This phenomenon has caused many countries to make efforts to recover the tourism sector to attract foreign tourists again. Each country has its own way of recovering the tourism sector after Covid-19. The strategy of recovering depends on the potential of each country. In this recovery effort, South Korea is utilizing digital diplomacy through the release of the tourism campaign ‘Visit Korea Year 2023-2024’ which is a form tourism promotion effort in the transition period. This research focuses on analyzing how South Korea utilize digital diplomacy to recover the South Korea tourism sector. The research method applied is descriptive-qualitative based on literature studies and interviews. The research results show that there is an effective use of digital diplomacy to recover the South Korea tourism sector through social media by implementing the components of engagement, listening real time dialogue, as well as the use of connected and collaborative promotions.